"دور الأتمتة الإلكترونية في تعزيز إيرادات الضريبة (دراسة تحليلية)" - عليوي وعد ظاهر (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study aims to explore the role of electronic automation in enhancing tax revenues, by analyzing contemporary digital technologies and their impact on tax collection efficiency and tax compliance. The study examined the digital transformation in tax administrations globally and the impact of implementing electronic systems on increasing tax revenues and reducing tax evasion. The study adopted a descriptive-analytical approach and used a sample of international studies and reports published between 2020 and 2025. The results showed that electronic automation contributes significantly to improving tax collection efficiency, leading to increases in tax revenues ranging from 15% to 35% in countries that have implemented these systems. The study also demonstrated that digital transformation reduces tax administration costs and improves tax compliance. The study recommends adopting a comprehensive strategy for digital transformation in tax administrations, with a focus on developing technical infrastructure and training human resources.